Malignant Peripheral Nerve Sheath Tumors are not a Feature of Neurofibromatosis Type 2 in the Unirradiated Patient. Issue 1 (20th July 2017) - King, Andrew T; Rutherford, Scott A; Hammerbeck-Ward, Charlotte; Lloyd, Simon K; Freeman, Simon R; Pathmanaban, Omar N; Kellett, Mark; Obholzer, Rupert; Afridi, Shazia; Axon, Patrick; Halliday, Dorothy; Parry, Allyson; et al.
Abstract: BACKGROUND: The published literature suggests that malignant peripheral nerve sheath tumors (MPNST) occur at increased frequency in neurofibromatosis type 2 (NF2). A recent review based on incidence data in North America showed that 1 per 1000 cerebellopontine angle nerve sheath tumors were malignant. OBJECTIVE: To determine whether MPNST occurred spontaneously in NF2 by reviewing our NF2 database. METHODS: The prospective database consists of 1253 patients with NF2. One thousand and nine are known to be alive at last follow-up. The presence and laterality/pathology of vestibular schwannoma at diagnosis and last follow-up was sought. RESULTS: There were no cases of spontaneous MPNST with 2114 proven (n = 1150) and presumed benign (n = 964) vestibular schwannomas found. Two patients had developed MPNST (1 presumed) after having previously undergone stereotactic radiosurgery for a vestibular schwannoma. CONCLUSION: In this series, and from the literature, malignant transformation of a vestibular schwannoma was not a feature of NF2 in the unirradiated patient. NF2 patients should not be told that they have an increased risk of malignant change in a vestibular schwannoma unless they undergo radiation treatment. However, very much larger datasets are required before it can be determined whether there is any association between NF2 and MPNST in the unirradiated patient.